Monitoring Kadar Glukosa Darah Non-Invasif Menggunakan Sensor Photoacoutic - Usman Umar; Imran Amin (Celebes Health Journal, 2019)
. Diabetes mellitus is a serious chronic disease that occurs in chronic metabolic disorders caused by the pancreas not being able to produce enough insulin or the body cannot use insulin effectively. Indonesia as the seventh-highest diabetes population in the world according to the International Diabetes Federation. Current blood glucose measurements generally use invasive techniques that take blood samples at the tip of the finger by injuring and done in clinics, health centers, and hospitals with high costs, so that the poor can not do routine checks. This study aims to develop a noninvasive system blood glucose measuring instrument. Tools with non-invasive systems use Photoacoustic Spectroscopy sensors in the range of values from the laser pulsation source (λ = 650 nm) that can detect glucose signals in the blood. Methods of developing this tool with stages include, preparation of tool making by conducting a literature study resulting in a theoretical model, developing a tool model by constructing a model through discussion Group Forum activities to obtain a hypothetic model, The results of this study produce glucose measuring instruments that are simple, easy to use and without taking blood samples to measure blood glucose levels routinely at a low cost. Validation of the measuring instrument by comparing invasive techniques with non-invasive techniques to obtain accuracy.